2019
DOI: 10.1093/brain/awy353
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte adenosine deaminase loss increases motor neuron toxicity in amyotrophic lateral sclerosis

Abstract: Using metabolic screening, Allen et al. identify an adenosine to inosine deamination defect in astrocytes from ALS patients. This defect is the result of reduced expression of adenosine deaminase, leading to increased susceptibility to adenosine-mediated toxicity. Astrocyte inosine supplementation reverses the motor neuron toxicity observed with patient astrocytes in co-culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 74 publications
12
111
0
Order By: Relevance
“…Using a fully humanized, spinal cord specific, co-culture platform to study ALS astrocyte/MN interactions, we were able to recapitulate previous studies 24,27,[63][64][65][66][67] showing that ALS hiPSC-A were toxic to hiPSC-MN in co-culture with several FALS and SALS lines. To identify specifically whether toxicity was mediated by the extracellular release of relevant toxic factors, we used a transwell system separating ALS hiPSC-A from hiPSC-M.…”
Section: Discussionsupporting
confidence: 72%
“…Using a fully humanized, spinal cord specific, co-culture platform to study ALS astrocyte/MN interactions, we were able to recapitulate previous studies 24,27,[63][64][65][66][67] showing that ALS hiPSC-A were toxic to hiPSC-MN in co-culture with several FALS and SALS lines. To identify specifically whether toxicity was mediated by the extracellular release of relevant toxic factors, we used a transwell system separating ALS hiPSC-A from hiPSC-M.…”
Section: Discussionsupporting
confidence: 72%
“…In vitro, cells tend to increase the de novo synthesis to compensate for a recycling deficit, a situation that is not physiologically possible in the brain, where the de novo pathway enzymes are only poorly active (12). This highlights the intrinsic ability of different cell types to mobilize alternative energy supplies to cope with bioenergetics stress -a property termed "metabolic flexibility" (34,35). However, 1 caveat of our study is that it mainly relied upon morphological observations of the neuronal network.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that, in addition to the degeneration of motor neurons, abnormal glial function occurs during ALS progression and contributes significantly to the pathogenesis of ALS. [44][45][46][47] To date, studies on adenosine homeostasis and its regulation in ALS are limited. The enzyme that converts adenosine to AMP (ADK) was found to be upregulated in the reactive astrocytes of patients with ALS 36 (Table 1).…”
Section: Adenosine Homeostasis In Alsmentioning
confidence: 99%
“…36 The suppression of ADK to elevate the aden-osine tone in the spinal cord thus may become a novel therapeutic approach for the development of treatments for ALS, as suggested for epileptic diseases 33,48 and schizophrenia. 49 Conversely, the expression of ADA has been found to be reduced in human astrocytes derived from patients with sporadic or the C9orf72 mutation-evoked ALS 44 ( Table 1). Such a decrease in ADA can lower inosine levels and subsequently impair the adenosine-/inosinemediated bioenergetic capacity (glycolysis) in astrocytes.…”
Section: Adenosine Homeostasis In Alsmentioning
confidence: 99%
See 1 more Smart Citation